Styles and rates of mesophotic reef accretion on a Caribbean insular slope - Sherman, Clark E.; Carlo, Milton; Tuohy, Evan; Adey, Walter H. (Coral Reefs, 2023)
Structural framework is fundamental to the concept of a coral-algal reef. However, our current understanding of reef framework is based largely upon studies of relatively shallow systems that formed at water depths of less than 30 m. There is comparatively limited information on deeper, mesophotic reef frameworks. Short drill cores collected at depths of ~ 50 m on the steep insular slope of southwest Puerto Rico allow for documentation of the composition and accretion rates of mesophotic reef framework. Framework is dominated by platy agariciid corals (Agaricia spp.) and autochthonous micrite (automicrite) with calcareous algae, corallines and peyssonnelids, forming a secondary component. Conspicuously, well-lithified automicrite constitutes a major structural and volumetric component of the framework. It is composed of magnesian calcite and displays irregular clotted, peloidal and fenestral fabrics, consistent with in situ formation. Radiocarbon ages of corals and automicrite indicate that they have formed recently (< 4 ka) and coevally in their current setting over a period of relative environmental stability. The steep slope gradient and associated dynamic oceanographic conditions may allow for extensive automicrite formation. Mesophotic reef accretion is occurring on the steep slope, though at slow rates of ~ 0.3 m ka−1.
Keywords: Autochthonous micrite (automicrite); Mesophotic coral ecosystem; Reef accretion; Reef framework

Coral Reefs of the WorldCoral Reefs of the Eastern Tropical PacificHolocene Reef Development in the Eastern Tropical Pacific - Toth, Lauren T.; Macintyre, Ian G.; Aronson, Richard B. (Springer Netherlands, 2016)
Contrary to early assessments, the eastern tropical Pacific (ETP) is not devoid of well-developed reefs. Significant accumulations of Holocene reef framework are present throughout the region, although they tend to be poorly consolidated, lack the submarine cementation common on most reefs elsewhere in the world, and are subject to considerable bioerosion. These reef frameworks began accreting as early as 7000 years ago. The thickest accumulations of Pocillopora frameworks occur in coastal areas of Mexico, Costa Rica, Panama, and Colombia, but reefs composed of massive corals—species of Porites, Pavona, or Gardineroseris—are present throughout the region. Reef development in the ETP is limited by a variety of characteristics of the physical environment. Because of high turbidity in most areas, reef development is generally restricted to less than ~10 m depth. The spatial extent of reefs in the ETP is also limited from the combined influences of wave action and upwelling. Most reefs in the ETP are only a few hectares in size and the best-developed reefs generally occur in areas sheltered from strong oceanic influence. Upwelling also influences long-term trends in reef development in the region. There does not appear to be a significant impact of upwelling on the millennial-scale growth rates of Panamanian reefs; however, reefs in upwelling environments typically have thinner frameworks than nearby reefs in non-upwelling environments. Furthermore, upwelling may have contributed to a historic shutdown of reef development in Costa Rica and Panama. Although both ecological and oceanographic disturbances have had some impact on the long-term development of reefs in the ETP, the most important control on reef development in this region throughout the Holocene has most likely been the El Niño–Southern Oscillation (ENSO). ENSO activity—especially that of the 1982–83 and 1997–98 El Niño events—has shaped the landscape of coral reefs across the ETP both in recent decades and in the past. Reefs in Pacific Panama and Costa Rica experienced a 2500-year hiatus in vertical growth beginning ~4100 years ago as a result of enhanced ENSO activity. Although the degree of framework accumulation and rate of reef accretion in some parts of the ETP are more similar to that of the western Atlantic than previously thought, the region still remains a marginal environment for reef development. Given the dominant role that climatic variability has played in controlling reef development in the past, the future of reefs in the ETP under accelerating climate change remains uncertain.
Keywords: El Niño; Latin American reefs; paleoecology; Reef accretion; Southern Oscillation; Upwelling

Accretion history of mid-Holocene coral reefs from the southeast Florida continental reef tract, USA - Stathakopoulos, A.; Riegl, B. M. (Coral Reefs, 2015)
Sixteen new coral reef cores were collected to better understand the accretion history and composition of submerged relict reefs offshore of continental southeast (SE) Florida. Coral radiometric ages from three sites on the shallow inner reef indicate accretion initiated by 8,050 Cal BP and terminated by 5,640 Cal BP. The reef accreted up to 3.75 m of vertical framework with accretion rates that averaged 2.53 m kyr-1. The reef was composed of a nearly even mixture of Acropora palmata and massive corals. In many cases, cores show an upward transition from massives to A. palmata and may indicate local dominance by this species prior to reef demise. Quantitative macroscopic analyses of reef clasts for various taphonomic and diagenetic features did not correlate well with depth/environmental-related trends established in other studies. The mixed coral framestone reef lacks a classical Caribbean reef zonation and is best described as an immature reef and/or a series of fused patch reefs; a pattern that is evident in both cores and reef morphology. This is in stark contrast to the older and deeper outer reef of the SE Florida continental reef tract. Accretion of the outer reef lasted from 10,695–8,000 Cal BP and resulted in a larger and better developed structure that achieved a distinct reef zonation. The discrepancies in overall reef morphology and size as well as the causes of reef terminations remain elusive without further study, yet they likely point to different climatic/environmental conditions during their respective accretion histories.
Keywords: Backstepping; Holocene; Reef accretion; Relict reef; SE Florida continental reef tract